Нова концепція збереження біоти Республіки Молдова. Червона книга Молдови (2015) - Коломійчук, В.П.; Попова, О.М. (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
Нова концепція збереження біоти Республіки Молдова. Червона книга Молдови (2015)